(untitled) (Intent Research Scientific Journal, 2023)
In recent years in several developed countries, including USA, Germany, China, Russia, Korea, UK, India, Japan, along with all the natural Sciences, improving the process of teaching chemistry is reflected in the work aimed at the harmonious management theory and practice, organization of training based on the sequence of “to know – to understand – to put into practice”, the development of the use of didactic games, selected in accordance with the age and interests of the pupils. In the future, as a result of educating the younger generation, who have thoroughly studied and perfectly mastered the scientific foundations of chemistry, they will help to solve many environmental, technological, food and a number of other production problems.